Quantitative cardiovascular magnetic resonance myocardial perfusion mapping to assess hyperaemic response to adenosine stress. (14th November 2020) - Kotecha, Tushar; Monteagudo, Juan Manuel; Martinez-Naharro, Ana; Chacko, Liza; Brown, James; Knight, Daniel; Knott, Kristopher D; Hawkins, Philip; Moon, James C; Plein, Sven; Xue, Hui; Kellman, Peter; et al.
Abstract: Aims: Assessment of hyperaemia during adenosine stress cardiovascular magnetic resonance (CMR) remains a clinical challenge with lack of a gold-standard non-invasive clinical marker to confirm hyperaemic response. This study aimed to validate maximum stress myocardial blood flow (SMBF) measured using quantitative perfusion mapping for assessment of hyperaemic response and compare this to current clinical markers of adenosine stress. Methods and results: Two hundred and eighteen subjects underwent adenosine stress CMR. A derivation cohort (22 volunteers) was used to identify a SMBF threshold value for hyperaemia. This was tested in a validation cohort (37 patients with suspected coronary artery disease) who underwent invasive coronary physiology assessment on the same day as CMR. A clinical cohort (159 patients) was used to compare SMBF to other physiological markers of hyperaemia [splenic switch-off (SSO), heart rate response (HRR), and blood pressure (BP) fall]. A minimum SMBF threshold of 1.43 mL/g/min was derived from volunteer scans. All patients in the coronary physiology cohort demonstrated regional maximum SMBF (SMBFmax) >1.43 mL/g/min and invasive evidence of hyperaemia. Of the clinical cohort, 93% had hyperaemia defined by perfusion mapping compared to 71% using SSO and 81% using HRR. There was no difference in SMBFmax in those with or without SSO (2.58 ± 0.89 vs. 2.54 ± 1.04 mL/g/min, P  = 0.84) but those with HRR had significantly higher SMBFmax (2.66 1.86 mL/g/min, P  < 0.001). HRR >15 bpm was superior to SSO in predicting adequate increase in SMBF (AUC 0.87 vs. 0.62, P  < 0.001). Conclusion: Adenosine-induced increase in myocardial blood flow is accurate for confirmation of hyperaemia during stress CMR studies and is superior to traditional, clinically used markers of adequate stress such as SSO and BP response.